Adoption of Alternate wetting and drying in Asia to save water and reduce methane emissions - CGIAR Research Program on Rice (2018)
Alternate wetting and drying is a water saving technology that enables irrigated rice cultivation with less water than the conventional practice of maintaining the field continuously flooded. This technology can reduce water input and GHG without yield penalty. AWD has been integrated in major national rice crop management guidelines in Vietnam, China and the Philippines and dissemination has started in all countries above. Several rice-producing countries mention AWD in their contributions to the Paris Agreement..